2017
DOI: 10.3390/fluids2020013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Loading Rate on the Relaxation and Recovery Ability of an Epoxy-Based Shape Memory Polymer

Abstract: Abstract:The majority of aerospace structural composites use thermoset resins for their processing flexibility, temperature capability, and environmental durability. In this study, the recovery behavior of Veriflex-E, an epoxy-based, thermosetting, thermally-triggered shape memory polymer (SMP) resin, is investigated in glassy (25 • C) and rubbery (130 • C) states, as a function of shape memory cycles, and as a means to evaluate its potential as a resin for a shape memory composite. At 25 • C, Veriflex-E exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Numerical analyses have shown that fibre elasticity is a key factor for the shape fixity of the composite, while the shape recovery also depends on the strain concentration near the fibre ends [3]. For the matrix, many polymers exhibit good SM behaviour but thermosetting resins generally show higher SM properties than thermoplastic, and epoxies are particularly suitable for this task [4,5]. SM epoxies also have better mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical analyses have shown that fibre elasticity is a key factor for the shape fixity of the composite, while the shape recovery also depends on the strain concentration near the fibre ends [3]. For the matrix, many polymers exhibit good SM behaviour but thermosetting resins generally show higher SM properties than thermoplastic, and epoxies are particularly suitable for this task [4,5]. SM epoxies also have better mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%